2019
DOI: 10.1002/nau.24016
|View full text |Cite
|
Sign up to set email alerts
|

Are psychological comorbidities important in the aetiology of lower urinary tract dysfunction—ICI‐RS 2018?

Abstract: Aims To review studies on the comorbid psychological symptoms and disorders in patients with lower urinary tract disorders (LUTD) over the life‐span, to analyse how they contribute toward the aetiology of LUTD and to discuss optimal service implementation. Materials and Methods A review of relevant literature was conducted and presented during the ICI‐RS meeting in 2018. Open questions and future directions were discussed. Results On the basis of current research, there is overwhelming evidence in all age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 69 publications
(141 reference statements)
1
23
0
2
Order By: Relevance
“…Stress is an important mental state to be assessed, but the literature is scant regarding this symptom in women with UI. Accumulation of stress may be due to social and functional impairments in women with UI, and other psychological symptoms may be related to stress 21 . In this study, we observed a high prevalence of mild, moderate, and severe stress within women with MD.…”
Section: Discussionsupporting
confidence: 47%
“…Stress is an important mental state to be assessed, but the literature is scant regarding this symptom in women with UI. Accumulation of stress may be due to social and functional impairments in women with UI, and other psychological symptoms may be related to stress 21 . In this study, we observed a high prevalence of mild, moderate, and severe stress within women with MD.…”
Section: Discussionsupporting
confidence: 47%
“…Recent calls to action from national societies reflect a similar sentiment from providers managing benign urologic disease. 49 Therefore, an optimal treatment approach could address physiological contributors to IC/BPS and simultaneously attune to patient cognitions, emotions, and behaviors that may impact symptoms and functional status. Regarding pain, psychological and environmental factors modulate nociception and treatment response and vice versa.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Mental health problems are found to be a consequence of UI; embarrassment, distress, and loss of self-esteem are often reported by those affected by the condition [ 14 ]. In addition, mental health problems may precede UI symptoms, especially nocturnal enuresis, due to the comorbidities associated with mental health problems (i.e., delayed bladder control, general development delay, and behavior problems) [ 13 ]. Further prospective longitudinal studies are needed to examine whether adolescents’ incontinence is an associated factor for later mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Management of adolescents with UI is superimposed considering the rapid physical, psychological, and developmental changes that occur in this population. Adolescents who carry UI from adolescence to adulthood can be considered similar to those with a chronic illness, in whom development, body image, and socialization are likely to be disrupted [ 13 , 14 ]. As effective treatments for UI are available, public awareness and early detection of UI among adolescents is critical.…”
Section: Introductionmentioning
confidence: 99%